Coupled CFD–DEM modelling of damage to a breakwater armour layer made of Antifer cubes exposed to regular waves - Matthieu Barcet; William Benguigui; Jérôme Laviéville; Michel Benoit; Pascal Fede; Thomas Bonometti (Ocean Engineering, 2026)

Fluopyram induces behavioural, hepatotoxic and metabolic alterations in fish at environmentally relevant concentrations - Lucie Bouly; Lisa Jacquin; Séverine Paris-Palacios; Camille Pasquet; Jean-Marc Bonmatin; Océane Delos; Lara Galès; Justine Bertrand-Michel; Floriant Bellvert; Marion Vivant; Pascal Laffaille; Anthony Lemarié; et al. (Journal of Hazardous Materials, 2026)

Diversification–specialisation dynamics in Madagascar’s clove landscapes: the role of rice land availability - Manon Desmurs; Julien Sarron; Elisa Rahantarivelo; Pascal Danthu; Éric Malézieux; Isabelle Michel (Agroforestry Systems, 2026)
Understanding why agroforestry systems are more or less diversified in species is essential for sustaining livelihoods and ecological functions in perennial-crop landscapes. In eastern Madagascar, clove-based agroforestry dominates upland production systems, yet field structure varies markedly across short distances. We clarified the association between landscape-scale rice production capacity and agroforestry diversification–specialisation dynamics in clove-dominated landscapes. We combined tree-inventory data from 54 plots with a quantitative proxy of village-level rice self-sufficiency across three neighbouring villages with contrasting access to irrigated lowlands. Four agroforestry system types, namely complex agroforests, diversified cash-oriented systems, clove-dominated systems and simple parklands, were identified through rule-based classification. Village-level access to irrigated lowlands was strongly associated with their distribution. In rice-surplus villages (Ampahibe, + 15% sufficiency), 94% of plots were complex agroforests integrating fruit and forest species (35% and 45% of stems, respectively) with mean species richness of 6.4 ± 3.0 species per plot. In rice-deficit uplands (Andampy, − 90% sufficiency), 50% of plots were clove-dominated systems where clove accounted for 70% of stems and species richness declined to 3.6 ± 2.1 species per plot. Contrary to expectations, within-village topography did not influence perennial species composition. Village-scale differentiation aligned with food-security constraints operating at household level rather than ecological sorting. Contemporary agroforestry configurations result from interactions between historical trajectories (colonial coffee plantations, farmer-led clove expansion, farmer-driven diversification since independence) and present-day rice availability, which filters diversification or specialisation trajectories. Maintaining agroforestry diversity in clove-producing regions depends as much on securing stable rice production systems as on managing perennial-crop markets.

Comparative evaluation of biocoagulant and bioflocculant properties of agricultural and green waste biomasses for water treatment - Océane Schwing; Pascal Labrousse; Ameni Ben Hassena; Magali Casellas-Français; Christelle Nabintu Kajoka; Michel Baudu (Journal of Water Process Engineering, 2026)

Limited human mobility during the Neolithic period in the Meuse and Mons basin in Belgium: multi-element isotopic analysis - IJk van Hattum; Marta Costas-Rodríguez; Kasper Hobin; Prudence Robert; Frank Vanhaecke; Elliot Van Maldegem; Hélène Collet; Pierre Cattelain; Michel Toussaint; Hans Vandendriessche; Samuel Bodé; Pascal Boeckx; et al. (Archaeological and Anthropological Sciences, 2026)
While the introduction of the Neolithic way of life in central Belgium around 5300 BCE is well-documented, the provenance and mobility patterns of Middle to Final Neolithic groups in southern Belgium (Wallonia) remain unclear. This work presents the first multi-element isotopic (strontium, 87 Sr/ 86 Sr; oxygen, δ 18 O; carbon, δ 13 C) data from prehistoric human dental enamel from the region. The study includes a total of 29 individuals, coming from karstic caves in the Meuse basin, the mining complex of Spiennes, and the megalithic tomb of Wéris II. The study also explores the variability of bioavailable strontium ratios in the geologically heterogeneous Meuse basin using modern plants. The analysis of multi-element isotopic data reveals high δ 18 O values and diverse 87 Sr/ 86 Sr ratios. The findings suggest that these individuals likely originated from or spent their childhood in present-day Belgium. Furthermore, the study highlights limited mobility during the Final Neolithic period, characterized by a combination of local residency and potential short-distance mobility or post-mortem movements. Overall, this study provides the first δ 18 O values from ancient human remains in the region and reshapes our understanding of human mobility during the Neolithic in present-day Belgium.

Towards 0.1mm/yr stability over decades for measuring sea level using tide gauges together with GNSS-based instruments? - Pascal Bonnefond; Olivier Laurain; Pierre Exertier; Michel Calzas; Christine Drezen; Lionel Fichen; Antoine Guillot; Thierry Guinle; Nicolas Picot (Marine Geodesy, 2026)

Patient-derived complex organoids are a critical tool to understand and explore pediatric malignant brain tumors - Marlène Deschuyter; Sophie Martin; Chinar Salmanli; Clémence Hubsch; Audrey Vincent; Samuel Meignan; Alessandro Furlan; Erika Cosset; Hélène Burckel; Georges Noel; Michel Salzet; Marie Duhamel; et al. (Cancer and Metastasis Reviews, 2026)

Effects of repeated exposure to full portions of non-alcoholic beers at home over several weeks on sensory perception, satisfaction, wanting, and purchase intent - Takahiro Wakihira; Michel Visalli; Pascal Schlich (Food Quality and Preference, 2026)

22 years of time-variable gravity field determination from GRACE and GRACE Follow-On: the CNES/GRGS RL05 solution - Jean-Michel Lemoine; Stéphane Bourgogne; Pascal Gégout; Franck Reinquin; Jean-Charles Marty; Flavien Mercier; Sylvain Loyer; Sean Bruinsma; Georges Balmino (Journal of Geodesy, 2026)
The GRACE and GRACE Follow-On (GRACE-FO) missions aim to track temporal changes in Earth's gravity field. Using data from these missions, CNES/GRGS has produced the “RL05” satellite-only series of geopotential solutions in spherical harmonics up to degree and order 90. These solutions are available at both monthly and 10-day temporal resolutions, covering the period from April 2002 to July 2025. These solutions were derived using a distinct processing strategy—particularly with respect to background models and solution stabilization techniques—compared to those adopted by most other groups involved in GRACE/GRACE-FO data processing. Nevertheless, the core parameter estimation approach remains fundamentally the same. The main differences with other processing centers are the combination of Satellite Laser Ranging (SLR) data from geodetic satellites with GRACE data at the normal equation level (and not as a substitution of low-degree SH coefficients) and the use of truncated singular value decomposition (TSVD) for the time-variable gravity (TVG) field solution. Examination of TVG time series over test areas such as the Caspian Sea and Iceland demonstrates the advantages of TSVD resolution over conventional unconstrained methods such as Cholesky decomposition, which require post-processing filtering. The DDK5 filter, for instance, produces a strong decrease in the restored signal from spherical harmonic degree 50, compared to approximately degree 70 for the TSVD solution. Our TSVD solution is also compared to mascon solutions, showing a commensurability of the signal content of the solutions, with the advantage of not relying on geophysical assumptions and of providing, on the oceans, a less constrained solution than mascons. Finally, an evaluation of the noise of these different solutions is carried out by estimating and comparing the errors of the solutions on the regions where the TVG signal is particularly weak. The noise is estimated at the level of 1.0 to 4.6 cm equivalent water height (EWH), depending on the resolution, for the DDK5-filtered RL06 solutions from CSR, JPL and GFZ, and at the level of 0.9–3.3 cm EWH for the COST-G, TUGRAZ and CNES-RL05-TSVD solutions.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Scale-up production of g-mangostin using Centrifugal Partition Chromatography - Anne-Marie Le Ray; Nadège Blon; Estelle Platon; Aurélie Guerin; Thomas Michel; Gregoire Audo; Guillaume Viault; Pascal Richomme (Phytochemistry Letters, 2025)

Resolved DEM-CFD coupling for wave-armour blocks interactions - Matthieu Barcet; William Benguigui; Jérôme Laviéville; Michel Benoit; Anthony Wachs; Pascal Fede; Thomas Bonometti (Ocean Engineering, 2025)

Effects of alcohol content information on sensory perception and satisfaction of full portions of regular beers and beer alternatives consumed at home - Takahiro Wakihira; Michel Visalli; Pascal Schlich (Food Quality and Preference, 2025)

Presence of antimicrobial residues in edible pig tissues after exposure to cross-contaminated feed: a case study with sulphadimethoxine/trimethoprim - Cristina Santos-Santórum Suárez; Pascal Sanders; Agnès Perrin-Guyomard; Michel Laurentie; Jean-François Taillandier; Marie-Pierre Lagrée; Murielle Gaugain; Alexis Viel (Food Additives & Contaminants: Part A, 2025)

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Soil-dependent fate of Klebsiella pneumoniae and Listeria monocytogenes after incorporation of digestates in soil microcosms - Sophie Michel-Le Roux; Christine Ziebal; Gaëtan Pinsard; Sophie Sadet-Bourgeteau; Anaïs Oliva; Pascal Piveteau (Applied Soil Ecology, 2025)

An approach to assess hazards in the vicinity of mountain and volcanic areas - Andre Michel Pouth Nkoma; Jorelle Larissa Meli’i; Marthe Mbond Ariane Gweth; Blaise Pascal Gounou Pokam; Michel Constant Njock; William Assatse Teikeu; Ibrahim Mbouombouo Ngapouth; Yvonne Poufone Koffi; Richie Kevin Wouako Wouako; Philippe Njandjock Nouck (Landslides, 2025)

New insight into the molecular etiopathogenesis of konzo: Cyanate could be a plausible neurotoxin contributing to konzo, contrary to thiocyanate - Marius Baguma; Sofie Kessels; Virginie Bito; Bert Brône; Antoine Triller; Stéphanie Maynard; Pascal Legendre; Jean-Michel Rigo; Hervé Le Corronc; Joelle Nsimire Chabwine (NeuroToxicology, 2024)

Corrigendum to “Spatial mechanistic modelling to simulate movements and contacts between wildlife and livestock in Southern Africa” [ecological modelling 498 (2024) /110863] - Florent Rumiano; Eve Miguel; Victor Dufleit; Pascal Degenne; Cedric Gaucherel; Hugo Valls-Fox; Michel de Garine-Wichatitsky; Edson Gandiwa; Alexandre Caron; Annelise Tran (Ecological Modelling, 2024)

Spatial mechanistic modelling to simulate movements and contacts between wildlife and livestock in Southern Africa - Florent Rumiano; Eve Miguel; Victor Dufleit; Pascal Degenne; Cédric Gaucherel; Hugo Valls-Fox; Michel de Garine-Wichatitsky; Edson Gandiwa; Alexandre Caron; Annelise Tran (Ecological Modelling, 2024)

Performance of carbon and nitrogen removal in a system combining an aerobic trickling filter followed by two stages of vertical flow treatment wetland - Kevin Maciejewski; Mathieu Gautier; Boram Kim; Philippe Michel; Pascal Molle; Remy Gourdon (Ecological Engineering, 2024)

Ease and Limitations in Using Environmental DNA to Track the Spread of Invasive Host–Parasite Complexes: A Case Study of the Freshwater Fish Pseudorasbora parva and the Cryptic Fungal Parasite Sphaerothecum destruens - Théo Deremarque; Rodolphe Elie Gozlan; Ravo Ravaozafindrasoa; Giuliano Mucci; Lucie Delalex; Jean-Michel Foissy; Michaël Cagnant; Mathieu Clair; Justina Givens; Fabienne Justy; Alice Valentini; Delphine Nicolas; et al. (Fishes, 2024)
The spread of non-native species threatens biodiversity and exacerbates societal challenges like food security. To address this, effective conservation programs require detection methods that are easy to implement, accurate, and non-invasive. Over the past 15 years, environmental DNA (eDNA) techniques have gained popularity, surpassing traditional sampling methods. In this context, our study focused on tracking the invasive host–pathogen complex Pseudorasbora parva and Sphaerothecum destruens using eDNA metabarcoding. We collected water samples from freshwater canals over five months in the Camargue region, and once in Corsica Island, both in southern France. Total DNA was extracted from filtered water samples, and PCR-amplicons were sequenced using Illumina or Nanopore technologies. Our results revealed a high detection rate of P. parva in lentic ecosystems, aligning with habitat preferences of this small freshwater fish. Additionally, the detection rate in Camargue increased in May and June, likely due to the peak of the spawning season, which leads to more DNA being released into the environment (i.e., concentration and interaction of individuals). While eDNA successfully detected this invasive fish, we were unable to detect its cryptic fungal parasite, S. destruens, highlighting the challenges of identifying intracellular and cryptic fungal pathogens through eDNA methods.

Intercomparison of very high-resolution surface soil moisture products over Catalonia (Spain) - Nadia Ouaadi; Lionel Jarlan; Michel Le Page; Mehrez Zribi; Giovani Paolini; Bouchra Ait Hssaine; Maria Jose Escorihuela; Pascal Fanise; Olivier Merlin; Nicolas Baghdadi; Aaron Boone (Remote Sensing of Environment, 2024)

Temporal precision and resolution of TDS and TCATA used with consumers - Michel Visalli; Benjamin Mahieu; Caroline Peltier; Sylvie Cordelle; Pascal Schlich (Food Quality and Preference, 2024)

Experimental investigation of a new CO2 refrigeration system arrangement for supermarket applications - Ana Paez; Bénédicte Ballot-Miguet; Benoit Michel; Pascal Tobaly; Rémi Revellin (International Journal of Refrigeration, 2024)

Single vs. sequential sensory evaluations of full portions of regular and non-alcoholic beers at home - Takahiro Wakihira; Michel Visalli; Pascal Schlich (Food Quality and Preference, 2024)

Product discrimination ability of temporal sensory evaluation methods used with consumers - Michel Visalli; Sylvie Cordelle; Noëlle Béno; Pascal Schlich (Food Quality and Preference, 2024)

An application of Electronic Monitoring System to optimize onboard observation protocols for estimating tropical tuna purse seine discards - Karine Briand; Philippe S. Sabarros; Alexandra Maufroy; Anne-Lise Vernet; Arthur Yon; Antoine Bonnieux; Michel Goujon; Pascal Bach (Regional Studies in Marine Science, 2023)

Use of temporal sensory evaluation methods with consumers: a position paper - Michel Visalli; Mara V Galmarini; Pascal Schlich (Current Opinion in Food Science, 2023)

Ground-based climate data show evidence of warming and intensification of the seasonal rainfall cycle during the 1960–2020 period in Yangambi, central Congo Basin - Emmanuel Kasongo Yakusu; Joris Van Acker; Hans Van de Vyver; Nils Bourland; José Mbifo Ndiapo; Théophile Besango Likwela; Michel Lokonda Wa Kipifo; Amand Mbuya Kankolongo; Jan Van den Bulcke; Hans Beeckman; Marijn Bauters; Pascal Boeckx; et al. (Climatic Change, 2023)
Meteorological stations are rare in central Africa, which leads to uncertainty in regional climatic trends. This is particularly problematic for the Congo Basin, where station coverage decreased significantly during the last few decades. Here, we present a digitized dataset of daily temperature and precipitation from the Yangambi biosphere reserve, covering the period 1960–2020 (61 years) and located in the heart of the Congo Basin. Our results confirm a long-term increase in temperature and temperature extremes since the 1960s, with strong upward trends since the early 1990s. Our results also indicate a drying trend for the dry season and intensification of the wet season since the early 2000s. Ongoing warming and increasing precipitation seasonality and intensity already have a significant impact on crop yields in Yangambi. This calls for urgent development of climate-smart and dynamic agriculture and agroforestry systems. We conclude that systematic digitization and climate recording in the Congo Basin will be critical to improve much-needed gridded benchmark datasets of climatic variables.

Assessment of the validity and reliability of temporal sensory evaluation methods used with consumers on controlled stimuli delivered by a gustometer - Michel Visalli; Noëlle Béno; Léna Nicolle; Pascal Schlich (Food Quality and Preference, 2023)

Indexes of individual repeatability and product discrimination in TDS and TCATA and their statistical inference - Cindy Frascolla; Michel Visalli; Hervé Cardot; Pascal Schlich (Food Quality and Preference, 2023)

Analyzing temporal dominance of sensations data with categorical functional data analysis - Caroline Peltier; Michel Visalli; Pascal Schlich; Hervé Cardot (Food Quality and Preference, 2023)

Services provided by multifunctional agroecosystems: Questions, obstacles and solutions - Alexia Stokes; Géraldine Bocquého; Pascal Carrere; Raphaël Conde Salazar; Marc Deconchat; Léo Garcia; Antoine Gardarin; Christian Gary; Cédric Gaucherel; Mamadou Gueye; Mickael Hedde; Françoise Lescourret; et al. (Ecological Engineering, 2023)

Hedonic valence of descriptive sensory terms as an indirect measure of liking: A preliminary study with red wines - Michel Visalli; Benjamin Mahieu; Magalie Dubois; Pascal Schlich (Food Quality and Preference, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

First steps towards FAIRization of product-focused sensory data - Michel Visalli; Pascal Schlich; Benjamin Mahieu; Arnaud Thomas; Magalie Weber; Elisabeth Guichard (Food Quality and Preference, 2023)

Temporal drivers of liking by period: A case study on lemon-flavored carbonated alcoholic drinks with consumers in natural settings - Takahiro Wakihira; Michel Visalli; Pascal Schlich (Food Quality and Preference, 2023)

Relevance of free-comment to describe wine temporal sensory perception: An application with panels varying in culture and expertise - Michel Visalli; Magalie Dubois; Pascal Schlich; François Ric; Jean-Marie Cardebat; Nikolaos Georgantzis (Food Quality and Preference, 2023)

Corrigendum to “Concurrent vs immediate retrospective temporal sensory data collection: A case study on lemon-flavoured carbonated alcoholic drinks” [Food Qual. Pref. 101 (2022) 104629] - Michel Visalli; Takahiro Wakihira; Pascal Schlich (Food Quality and Preference, 2023)

Validation of a LC-MS/MS method for the quantitative analysis of four antibiotics in pig tissues and plasma to assess the risk of transfer of residues to edible matrices after exposure to cross-contaminated feed - Cristina Santos-Santórum Suárez; Pascal Sanders; Agnès Perrin-Guyomard; Dominique Hurtaud-Pessel; Michel Laurentie; Alexis Viel; Jean-François Taillandier; Marie-Pierre Lagree; Murielle Gaugain (Food Additives & Contaminants: Part A, 2022)

Species and population genomic differentiation in Pocillopora corals (Cnidaria, Hexacorallia) - Didier Aurelle; Marine Pratlong; Nicolas Oury; Anne Haguenauer; Pauline Gélin; Hélène Magalon; Mehdi Adjeroud; Pascal Romans; Jeremie Vidal-Dupiol; Michel Claereboudt; Camille Noûs; Lauric Reynes; et al. (Genetica, 2022)

Bias in hydraulic head measurements from multilevel vibrating-wire piezometers with excessively permeable backfill - Nathan L. Young; Jean-Michel Lemieux; Pascal Locat; Denis Demers; Hugo Delottier; Laura Mony (Hydrogeology Journal, 2022)

First glance at the molecular etiology of hearing loss in French-Canadian families from Saguenay-Lac-Saint-Jean’s founder population - Tania Cruz Marino; Jessica Tardif; Josianne Leblanc; Janie Lavoie; Pascal Morin; Michel Harvey; Marie-Jacqueline Thomas; Annabelle Pratte; Nancy Braverman (Human Genetics, 2022)

Coming from elsewhere: the preponderance of introduced plant species in agroforestry systems on the east coast of Madagascar - Pascal Danthu; Isabelle Michel; Stéphanie M. Carrière; Vanesse Labeyrie; Bakolimalala Rakouth; Julien Sarron; Juliette Mariel; Dominique Lasserre; Eric Penot (Agroforestry Systems, 2022)

Validating a New GNSS-Based Sea Level Instrument (CalNaGeo) at Senetosa Cape - Pascal Bonnefond; Olivier. Laurain; Pierre Exertier; Michel Calzas; Thierry Guinle; Nicolas Picot (Marine Geodesy, 2022)

Not all species will migrate poleward as the climate warms: The case of the seven baobab species in Madagascar - Mario M. Tagliari; Pascal Danthu; Jean‐Michel Leong Pock Tsy; Cyrille Cornu; Jonathan Lenoir; Vítor Carvalho‐Rocha; Ghislain Vieilledent (Global Change Biology, 2021)
It is commonly accepted that species should move toward higher elevations and latitudes to track shifting isotherms as climate warms. However, temperature might not be the only limiting factor determining species distribution. Species might move to opposite directions to track changes in other climatic variables. Here, we used an extensive occurrence data set and an ensemble modelling approach to model the climatic niche and to predict the distribution of the seven baobab species (genus Adansonia ) present in Madagascar. Using climatic projections from three global circulation models, we predicted species’ future distribution and extinction risk for 2055 and 2085 under two representative concentration pathways (RCPs) and two dispersal scenarios. We disentangled the role of each climatic variable in explaining species range shift looking at relative variable importance and future climatic anomalies. Four baobab species ( Adansonia rubrostipa , Adansonia madagascariensis , Adansonia perrieri¸ and Adansonia suarezensis ) could experience a severe range contraction in the future (>70% for year 2085 under RCP 8.5, assuming a zero‐dispersal hypothesis). For three out of the four threatened species, range contraction was mainly explained by an increase in temperature seasonality, especially in the North of Madagascar, where they are currently distributed. In tropical regions, where species are commonly adapted to low seasonality, we found that temperature seasonality will generally increase. It is, thus, very likely that many species in the tropics will be forced to move equatorward to avoid an increase in temperature seasonality. Yet, several ecological (e.g., equatorial limit, or unsuitable deforested habitat) or geographical barriers (absence of lands) could prevent species to move equatorward, thus increasing the extinction risk of many tropical species, like endemic baobab species in Madagascar.

COVID-19 or not COVID-19? Compared characteristics of patients hospitalized for suspected COVID-19 - Thomas Rogier; Isabelle Eberl; Florian Moretto; Thibault Sixt; François-Xavier Catherine; Clémentine Estève; Maroua Abdallahoui; Lucile Behague; Antoine Coussement; Lucas Mathey; Sophie Mahy; Marielle Buisson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Part-time work and other occupational risk factors for suicide among working women in the Swiss National Cohort - Pascal Wild; Nicolas Bovio; Irina Guseva Canu; Matthias Egger; Adrian Spörri; Marcel Zwahlen; Milo Puhan; Matthias Bopp; Martin Röösli; Michel Oris; Murielle Bochud (International Archives of Occupational and Environmental Health, 2021)
Objective The aim of this study was to describe the factors associated with mortality by suicide among working women focusing on work-related factors. Methods The study population consisted in all Swiss residents recorded in the 1990 and/or the 2000 compulsory national censuses and were linked to emigration and mortality registers. We selected all women aged 18–65 and at work at the official census dates. Following work-related variables were available: socio-economic status, weekly hours of work, the sector of activity and the job title coded according to the International Standard Classification of Occupations (ISCO). The risk of suicide was modelled using negative binomial regression. Results The cohort comprised 1,771,940 women and 2526 deaths by suicide corresponding to 24.9 million person-years. The most significant non-occupational predictors of suicide were age, period, civil status, religion, nationality and geographical regions. Adjusted on these factors, part-time work was associated with increased suicide rates. According to job codes, health and social activities, in particular care-worker had the highest suicide risks. Conclusion Suicide among working women depended on work-related factors even taking into account other socio-demographic factors.

Multi-method investigation of mass transfer mechanisms in a retrogressive clayey landslide (Harmalière, French Alps) - Sylvain Fiolleau; Denis Jongmans; Gregory Bièvre; Guillaume Chambon; Pascal Lacroix; Agnès Helmstetter; Marc Wathelet; Michel Demierre (Landslides, 2021)

Longitudinal predictors of bronchial hyperresponsiveness and FEV1 decline in bakers - Valérie Demange; Michel Grzebyk; Michel Héry; Nicole Massin; Christophe Paris; Pascal Wild (International Archives of Occupational and Environmental Health, 2021)

Young and mature males have similar energy expenditure during the rut in a trophy-hunted population of Mediterranean mouflon - Gilles Bourgoin; Alice Laurent; Pascal Marchand; Jeanne Duhayer; Marie-Thérèse Poirel; Patricia Michel; Christian Itty; Mathieu Garel (Mammalian Biology, 2021)

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

Characterizing Exposure to and Sharing Knowledge of Drivers of Environmental Change in the St. Lawrence System in Canada - David Beauchesne; Rémi M. Daigle; Steve Vissault; Dominique Gravel; Andréane Bastien; Simon Bélanger; Pascal Bernatchez; Marjolaine Blais; Hugo Bourdages; Clément Chion; Peter S. Galbraith; Benjamin S. Halpern; et al. (Frontiers in Marine Science, 2020)

Horizontal flows of nitrogen, potassium, and carbon in urban vegetables gardens of Bobo Dioulasso, Burkina Faso - Désiré Jean-Pascal Lompo; Emmanuel Compaoré; Michel Papaoba Sedogo; Martina Melapie; C. L. Bielders; Eva Schlecht; Andreas Buerkert (Nutrient Cycling in Agroecosystems, 2019)

The baobabs of the Comoro Islands: some biogeographical factors towards the protection and conservation of a neglected asset - Maoulida Mohamed Abdillahi; Cyrille Cornu; Raïma Fadul; Michel Charpentier; Edmond Roger; Bakolimalala Rakouth; Jean-Michel Leong Pock Tsy; Pascal Danthu (Tropical Ecology, 2019)

Hydrodynamic time parameters response to meteorological and physical forcings: toward a stagnation risk assessment device in coastal areas - Marion Drouzy; Pascal Douillet; Jean-Michel Fernandez; Christel Pinazo (Ocean Dynamics, 2019)

Clove based cropping systems on the east coast of Madagascar: how history leaves its mark on the landscape - Natacha Arimalala; Eric Penot; Thierry Michels; Vonjison Rakotoarimanana; Isabelle Michel; Harisoa Ravaomanalina; Edmond Roger; Michel Jahiel; Jean-Michel Leong Pock Tsy; Pascal Danthu (Agroforestry Systems, 2019)

Paleoclimate variations and impact on groundwater recharge in multi-layer aquifer systems using a multi-tracer approach (northern Aquitaine basin, France) - Marc Saltel; Romain Rebeix; Bertrand Thomas; Michel Franceschi; Bernard Lavielle; Pascal Bertran (Hydrogeology Journal, 2019)

Parental sex allocation and sex-specific survival drive offspring sex ratio bias in little owls - Matthias Tschumi; Jolanda Humbel; Joscha Erbes; Julien Fattebert; Jochen Fischer; Gerhard Fritz; Barbara Geiger; Ronald van Harxen; Bernd Hoos; Johanna Hurst; Lars Bo Jacobsen; Herbert Keil; et al. (Behavioral Ecology and Sociobiology, 2019)

The protective role of liver X receptor (LXR) during fumonisin B1-induced hepatotoxicity - Marion Régnier; Arnaud Polizzi; Céline Lukowicz; Sarra Smati; Frédéric Lasserre; Yannick Lippi; Claire Naylies; Joelle Laffitte; Colette Bétoulières; Alexandra Montagner; Simon Ducheix; Pascal Gourbeyre; et al. (Archives of Toxicology, 2019)

Comparison of metabolic profiles and bioactivities of the leaves of three edible Congolese Hibiscus species - Paulin Mutwale Kapepula; Nadege Kabamba Ngombe; Pascal Tshisekedi Tshibangu; César Tsumbu; Thierry Franck; Ange Mouithys-Mickalad; Dieudonné Mumba; Désiré Tshala-Katumbay; Didier Serteyn; Monique Tits; Luc Angenot; Pascal Dibungi T. Kalenda; et al. (Natural Product Research, 2017)

Nest design in a changing world: Great tit Parus major nests from a Mediterranean city environment as a case study - Marcel M. Lambrechts; Anne Charmantier; Virginie Demeyrier; Annick Lucas; Samuel Perret; Matthieu Abouladzé; Michel Bonnet; Coline Canonne; Virginie Faucon; Stéphanie Grosset; Gaëlle le Prado; Frédéric Lidon; et al. (Urban Ecosystems, 2017)

Antioxidant potentiality of three herbal teas consumed in Bandundu rural areas of Congo - Paulin Mutwale Kapepula; Patricia Mbombo Mungitshi; Thierry Franck; Ange Mouithys-Mickalad; Dieudonné Mumba Ngoyi; Pascal Dibungi T. Kalenda; Nadege Kabamba Ngombe; Didier Serteyn; Monique Tits; Michel Frédérich; Jean-Jacques Tamfum Muyembe (Natural Product Research, 2017)

Erratum to: Fluids preserved in variably altered graphitic pelitic schists in the Dufferin Lake Zone, south-central Athabasca Basin, Canada: implications for graphite loss and uranium deposition - Marjolaine Pascal; Marie-Christine Boiron; Kevin Ansdell; Irvine R. Annesley; Tom Kotzer; Dan Jiricka; Michel Cuney (Mineralium Deposita, 2016)

Fluids preserved in variably altered graphitic pelitic schists in the Dufferin Lake Zone, south-central Athabasca Basin, Canada: implications for graphite loss and uranium deposition - Marjolaine Pascal; Marie-Christine Boiron; Kevin Ansdell; Irvine R. Annesley; Tom Kotzer; Dan Jiricka; Michel Cuney (Mineralium Deposita, 2016)

Fully Equipped to Succeed: Migratory Contingents Seen as an Intrinsic Potential for Striped Bass to Exploit a Heterogeneous Environment Early in Life - Olivier Morissette; Frédéric Lecomte; Guy Verreault; Michel Legault; Pascal Sirois (Estuaries and Coasts, 2016)

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

Morphological and functional characterisation of the burrow systems of six earthworm species (Lumbricidae) - Yvan Capowiez; Nicolas Bottinelli; Stéphane Sammartino; Eric Michel; Pascal Jouquet (Biology and Fertility of Soils, 2015)

The efficiency of RNA interference for conferring stable resistance to plum pox virus - Michel Ravelonandro; Ralph Scorza; Hily Jean Michel; Pascal Briard (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Impact of climate change on the hydrogeology of two basins in northern France - Florence Habets; Julien Boé; Michel Déqué; Agnès Ducharne; Simon Gascoin; Ali Hachour; Eric Martin; Christian Pagé; Eric Sauquet; Laurent Terray; Dominique Thiéry; Ludovic Oudin; et al. (Climatic Change, 2013)

The simulation of European heat waves from an ensemble of regional climate models within the EURO-CORDEX project - Robert Vautard; Andreas Gobiet; Daniela Jacob; Michal Belda; Augustin Colette; Michel Déqué; Jesús Fernández; Markel García-Díez; Klaus Goergen; Ivan Güttler; Tomáš Halenka; Theodore Karacostas; et al. (Climate Dynamics, 2013)

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Impact of two root systems, earthworms and mycorrhizae on the physical properties of an unstable silt loam Luvisol and plant production - Roxane Kohler-Milleret; Renée-Claire Le Bayon; Claire Chenu; Jean-Michel Gobat; Pascal Boivin (Plant and Soil, 2013)

Coexistence of Passive and Proton Antiporter-Mediated Processes in Nicotine Transport at the Mouse Blood–Brain Barrier - Salvatore Cisternino; Hélène Chapy; Pascal André; Maria Smirnova; Marcel Debray; Jean-Michel Scherrmann (The AAPS Journal, 2013)

Nest-box size influences where secondary-cavity exploiters roost and nest: a choice experiment - Marcel M. Lambrechts; Matthieu Abouladzé; Michel Bonnet; Virginie Demeyrier; Claire Doutrelant; Virginie Faucon; Gaëlle le Prado; Frédéric Lidon; Thierry Noell; Pascal Pagano; Philippe Perret; Stéphane Pouplard; et al. (Journal of Ornithology, 2013)

Dramatic increase in the Zembretta Yelkouan shearwater breeding population following ship rat eradication spurs interest in managing a 1500-year old invasion - Karen Bourgeois; Ridha Ouni; Michel Pascal; Sylvain Dromzée; Damien Fourcy; Awatef Abiadh (Biological Invasions, 2013)

On regularized time varying gravity field models based on grace data and their comparison with hydrological models - Mehdi Eshagh; Jean-Michel Lemoine; Pascal Gegout; Richard Biancale (Acta Geophysica, 2013)

Folic acid supplementation, MTHFR and MTRR polymorphisms, and the risk of childhood leukemia: the ESCALE study (SFCE) - Alicia Amigou; Jérémie Rudant; Laurent Orsi; Stéphanie Goujon-Bellec; Guy Leverger; André Baruchel; Yves Bertrand; Brigitte Nelken; Geneviève Plat; Gérard Michel; Stéphanie Haouy; Pascal Chastagner; et al. (Cancer Causes & Control, 2012)

Disparity in 90Sr and 137Cs uptake in Alpine plants: phylogenetic effect and Ca and K availability - Thomas Guillaume; Fabienne Chawla; Philipp Steinmann; Jean-Michel Gobat; Pascal Froidevaux (Plant and Soil, 2012)

Postural control and ventilatory drive during voluntary hyperventilation and carbon dioxide rebreathing - Pascal David; David Laval; Jérémy Terrien; Michel Petitjean (European Journal of Applied Physiology, 2012)

Pesticide exposure in farming and forestry and the risk of uveal melanoma - Thomas Behrens; Elsebeth Lynge; Ian Cree; Jean-Michel Lutz; Mikael Eriksson; Pascal Guénel; Franco Merletti; Maria Morales-Suarez-Varela; Noemia Afonso; Aivars Stengrevics; Joëlle Févotte; Svend Sabroe; et al. (Cancer Causes & Control, 2012)

Computing with bacterial constituents, cells and populations: from bioputing to bactoputing - Vic Norris; Abdallah Zemirline; Patrick Amar; Jean Nicolas Audinot; Pascal Ballet; Eshel Ben-Jacob; Gilles Bernot; Guillaume Beslon; Armelle Cabin; Eric Fanchon; Jean-Louis Giavitto; Nicolas Glade; et al. (Theory in Biosciences, 2011)

GABAA Receptor and Glycine Receptor Activation by Paracrine/Autocrine Release of Endogenous Agonists: More Than a Simple Communication Pathway - Herve Le-Corronc; Jean-Michel Rigo; Pascal Branchereau; Pascal Legendre (Molecular Neurobiology, 2011)

Prorocentrum rivalis sp. nov. (Dinophyceae) and its phylogenetic affinities inferred from analysis of a mixed morphological and LSU rRNA data set - David Delmail; Pascal Labrousse; Philippe Crassous; Philippe Hourdin; Mathieu Guri; Michel Botineau (Biologia, 2011)

How might science misdirect policy? Insights into the threats and consequences of invasive species - Martin A. Schlaepfer; Michel Pascal; Mark A. Davis (Journal of Consumer Protection and Food Safety, 2011)

Differential responses of Myriophyllum alterniflorum DC (Haloragaceae) organs to copper: physiological and developmental approaches - David Delmail; Pascal Labrousse; Philippe Hourdin; Laure Larcher; Christian Moesch; Michel Botineau (Hydrobiologia, 2011)

Links Between Cyclosporin Exposure in Tissues and Graft-Versus-Host Disease in Pediatric Bone Marrow Transplantation: Analysis by a PBPK Model - Cécile Gérard; Nathalie Bleyzac; Pascal Girard; Gilles Freyer; Yves Bertrand; Michel Tod (Pharmaceutical Research, 2011)

Influence of Dosing Schedule on Organ Exposure to Cyclosporin in Pediatric Hematopoietic Stem Cell Transplantation: Analysis with a PBPK Model - Cécile Gérard; Nathalie Bleyzac; Pascal Girard; Gilles Freyer; Yves Bertrand; Michel Tod (Pharmaceutical Research, 2010)

Hormonal exposures and the risk of uveal melanoma - Thomas Behrens; Linda Kaerlev; Ian Cree; Jean-Michel Lutz; Noemia Afonso; Mikael Eriksson; Pascal Guénel; Franco Merletti; Maria Morales-Suarez-Varela; Aivars Stengrevics; Svend Sabroe; Diane Cyr; et al. (Cancer Causes & Control, 2010)

High-efficiency derivation of human embryonic stem cell lines following pre-implantation genetic diagnosis - Philippe Tropel; Johana Tournois; Julien Côme; Christine Varela; Céline Moutou; Pascal Fragner; Michel Cailleret; Yacine Laâbi; Marc Peschanski; Stéphane Viville (In Vitro Cellular & Developmental Biology - Animal, 2010)

Proliferating cell nuclear antigen in gonad and associated storage tissue of the Pacific oyster Crassostrea gigas: seasonal immunodetection and expression in laser microdissected tissues - Alban Franco; Aude Jouaux; Michel Mathieu; Pascal Sourdaine; Christophe Lelong; Kristell Kellner; Clothilde Heude Berthelin (Cell and Tissue Research, 2010)

Phylogeography of the introduced species Rattus rattus in the western Indian Ocean, with special emphasis on the colonization history of Madagascar - Charlotte Tollenaere; Carine Brouat; Jean‐Marc Duplantier; Lila Rahalison; Soanandrasana Rahelinirina; Michel Pascal; Hélène Moné; Gabriel Mouahid; Herwig Leirs; Jean‐François Cosson (Journal of Biogeography, 2010)
Aim To describe the phylogeographic patterns of the black rat, Rattus rattus , from islands in the western Indian Ocean where the species has been introduced (Madagascar and the neighbouring islands of Réunion, Mayotte and Grande Comore), in comparison with the postulated source area (India). Location Western Indian Ocean: India, Arabian Peninsula, East Africa and the islands of Madagascar, Réunion, Grande Comore and Mayotte. Methods Mitochondrial DNA (cytochrome b , tRNA and D‐loop, 1762 bp) was sequenced for 71 individuals from 11 countries in the western Indian Ocean. A partial D‐loop (419 bp) was also sequenced for eight populations from Madagascar (97 individuals), which were analysed in addition to six previously published populations from southern Madagascar. Results Haplotypes from India and the Arabian Peninsula occupied a basal position in the phylogenetic tree, whereas those from islands were distributed in different monophyletic clusters: Madagascar grouped with Mayotte, while Réunion and Grand Comore were present in two other separate groups. The only exception was one individual from Madagascar (out of 190) carrying a haplotype that clustered with those from Réunion and South Africa. ‘Isolation with migration’ simulations favoured a model with no recurrent migration between Oman and Madagascar. Mismatch distribution analyses dated the expansion of Malagasy populations on a time‐scale compatible with human colonization history. Higher haplotype diversity and older expansion times were found on the east coast of Madagascar compared with the central highlands. Main conclusions Phylogeographic patterns supported the hypothesis of human‐mediated colonization of R. rattus from source populations in either the native area (India) or anciently colonized regions (the Arabian Peninsula) to islands of the western Indian Ocean. Despite their proximity, each island has a distinct colonization history. Independent colonization events may have occurred simultaneously in Madagascar and Grande Comore, whereas Mayotte would have been colonized from Madagascar. Réunion was colonized independently, presumably from Europe. Malagasy populations may have originated from a single successful colonization event, followed by rapid expansion, first in coastal zones and then in the central highlands. The congruence of the observed phylogeographic pattern with human colonization events and pathways supports the potential relevance of the black rat in tracing human history.

Harmonin-b, an actin-binding scaffold protein, is involved in the adaptation of mechanoelectrical transduction by sensory hair cells - Nicolas Michalski; Vincent Michel; Elisa Caberlotto; Gaelle M. Lefèvre; Alexander F. J. van Aken; Jean-Yves Tinevez; Emilie Bizard; Christophe Houbron; Dominique Weil; Jean-Pierre Hardelin; Guy P. Richardson; Corné J. Kros; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Taking into account local practices and indigenous knowledge in an emergency conservation context in Madagascar - Chloé N. Marie; Nicole Sibelet; Michel Dulcire; Minah Rafalimaro; Pascal Danthu; Stéphanie M. Carrière (Biodiversity and Conservation, 2009)

Chloroplast DNA phylogeography suggests a West African centre of origin for the baobab, Adansonia digitata L. (Bombacoideae, Malvaceae) - JEAN‐MICHEL LEONG POCK TSY; ROSELYNE LUMARET; DIANA MAYNE; ABDALLAHI OULD MOHAMED VALL; YAHIA I. M. ABUTABA; MAURICE SAGNA; SOAHARIN’NY ONY RAKOTONDRALAMBO RAOSETA; PASCAL DANTHU (Molecular Ecology, 2009)
The African baobab ( Adansonia digitata L.) is an emblematic, culturally important, and physically huge tropical tree species whose natural geographical distribution comprises most of tropical Africa, but also small patches of southern Arabia, and several Atlantic and Indian Ocean islands surrounding the African continent, notably including Madagascar. We analysed the polymerase chain reaction–restriction fragment length polymorphism of five chloroplast DNA fragments obtained from 344 individuals of A. digitata collected from 74 populations covering the entire extant distribution range of the species. Our goal was to reconstruct the phylogeographical history of the species and, if possible, to identify its centre of origin, which has been a subject of controversy for many decades. We identified five haplotypes whose distribution is clearly geographically structured. Using several species of Adansonia and of closely related genera as outgroups, the haplotypes showed a clear phylogeographical pattern of three groups. Two are phylogenetically related to the outgroup taxa, and are distributed in West Africa. The third group is substantially more differentiated genetically from outgroup species, and it corresponds to southern and eastern Africa, Arabia and the Indian Ocean islands, including Madagascar. According to our results, the tetraploid A. digitata , or its diploid progenitor, probably originated in West Africa and migrated subsequently throughout the tropical parts of that continent, and beyond, by natural and human‐mediated terrestrial and overseas dispersal.

Habitat use and potential interactions between the house mouse and lesser white-toothed shrew on an island undergoing habitat restoration - Michel Pascal; Olivier Lorvelec; Frédéric Bioret; Pierre Yésou; Daniel Simberloff (Mammal Research, 2009)

Impact of carrot resistance on development of the Alternaria leaf blight pathogen (Alternaria dauci) - Cora Boedo; Valérie Le Clerc; Mathilde Briard; Philippe Simoneau; Michel Chevalier; Sonia Georgeault; Pascal Poupard (European Journal of Plant Pathology, 2008)

Mining and Other Threats to the New Caledonia Biodiversity Hotspot - MICHEL PASCAL; BERTRAND RICHER DE FORGES; HERVÉ LE GUYADER; DANIEL SIMBERLOFF (Conservation Biology, 2008)

W–Au skarns in the Neo-Proterozoic Seridó Mobile Belt, Borborema Province in northeastern Brazil: an overview with emphasis on the Bonfim deposit - João Adauto Souza Neto; Jean Michel Legrand; Marcel Volfinger; Marie-Lola Pascal; Philippe Sonnet (Mineralium Deposita, 2008)

Role of the 25–26 nt siRNA in the resistance of transgenic Prunus domestica graft inoculated with plum pox virus - Jiban Kumar Kundu; Pascal Briard; Jean Michel Hily; Michel Ravelonandro; Ralph Scorza (Virus Genes, 2008)

Invasive Rodent Eradication on Islands - GREGG HOWALD; C. JOSH DONLAN; JUAN PABLO GALVÁN; JAMES C. RUSSELL; JOHN PARKES; ARACELI SAMANIEGO; YIWEI WANG; DICK VEITCH; PIERO GENOVESI; MICHEL PASCAL; ALAN SAUNDERS; BERNIE TERSHY (Conservation Biology, 2007)
Invasive mammals are the greatest threat to island biodiversity and invasive rodents are likely responsible for the greatest number of extinctions and ecosystem changes. Techniques for eradicating rodents from islands were developed over 2 decades ago. Since that time there has been a significant development and application of this conservation tool. We reviewed the literature on invasive rodent eradications to assess its current state and identify actions to make it more effective. Worldwide, 332 successful rodent eradications have been undertaken; we identified 35 failed eradications and 20 campaigns of unknown result. Invasive rodents have been eradicated from 284 islands (47,628 ha). With the exception of two small islands, rodenticides were used in all eradication campaigns. Brodifacoum was used in 71% of campaigns and 91% of the total area treated. The most frequent rodenticide distribution methods (from most to least) are bait stations, hand broadcasting, and aerial broadcasting. Nevertheless, campaigns using aerial broadcast made up 76% of the total area treated. Mortality of native vertebrates due to nontarget poisoning has been documented, but affected species quickly recover to pre‐eradication population levels or higher. A variety of methods have been developed to mitigate nontarget impacts, and applied research can further aid in minimizing impacts. Land managers should routinely remove invasive rodents from islands Mus musculus ), island size may no longer be the limiting factor for rodent eradications; rather, social acceptance and funding may be the main challenges. To be successful, large‐scale rodent campaigns should be integrated with programs to improve the livelihoods of residents, island biosecurity, and reinvasion response programs.

Evaluation of Uncertainty Parameters Estimated by Different Population PK Software and Methods - Céline Dartois; Annabelle Lemenuel-Diot; Christian Laveille; Brigitte Tranchand; Michel Tod; Pascal Girard (Journal of Pharmacokinetics and Pharmacodynamics, 2007)

Establishing Causes of Eradication Failure Based on Genetics: Case Study of Ship Rat Eradication in Ste. Anne Archipelago - JAWAD ABDELKRIM; MICHEL PASCAL; SARAH SAMADI (Conservation Biology, 2007)
Determining the causes of a failed eradication of a pest species is important because it enables an argued adjustment of the methodologies used and the improvement of the protocols for future attempts. We examined how molecular monitoring can help distinguish between the two main reasons for an eradication failure (i.e., survival of some individuals vs. recolonization after eradication). We investigated genetic variation in seven microsatellite loci in ship rat (Rattus rattus) populations from four islets off the Martinique coast (French Caribbean). In 1999 an eradication attempt was conducted on the four islets. Three years later rats were observed again on two of them. We compared the genetic signatures of the populations before and after the eradication attempt. On one of the islands, the new rat population was likely a subset of the pre‐eradication population. A weak genetic differentiation was found between them, with almost no new alleles observed in the new population and moderate F ST values (0.15). Moreover, assignment procedures clustered the two populations together. In contrast, on the other islet, many new alleles were observed after the eradication attempt, resulting in an increase in genetic diversity (from 2.57 to 3.57 mean number of alleles per locus) and strong F ST values (0.39). Moreover, genetic clustering clearly separated the two samples (i.e., before and after the eradication attempt) in two different populations. Thus, to achieve long‐term eradication on these islets, it seems necessary to redevelop the eradication procedure to avoid individuals surviving and to prevent reinvasion, probably from the mainland, by installing permanent trapping and poisoning devices and conducting regular monitoring. We strongly encourage wildlife managers conducting eradication campaigns to integrate molecular biological tools in their protocols, which can be done easily for most common invasive species.

Influence of Dyslipidemia on Moxidectin Distribution in Plasma Lipoproteins and on its Pharmacokinetics - Mohamad Firas Bassissi; Michel Alvinerie; Pascal Guy Pierre Martin; Bertrand Perret; Anne Lespine (Pharmaceutical Research, 2006)

Genetic divergence in the small Indian mongoose ( Herpestes auropunctatus ), a widely distributed invasive species - CARL‐GUSTAF THULIN; DANIEL SIMBERLOFF; ARIJANA BARUN; GARY MCCRACKEN; MICHEL PASCAL; M. ANWARUL ISLAM (Molecular Ecology, 2006)
The combination of founder events, random drift and new selective forces experienced by introduced species typically lowers genetic variation and induces differentiation from the ancestral population. Here, we investigate microsatellite differentiation between introduced and native populations of the small Indian mongoose ( Herpestes auropunctatus ). Many expectations based on introduction history, such as loss of alleles and relationships among populations, are confirmed. Nevertheless, when applying population assignment methods to our data, we observe a few specimens that are incorrectly assigned and/or appear to have a mixed ancestry, despite estimates of substantial population differentiation. Thus, we suggest that population assignments of individuals should be viewed as tentative and that there should be agreement among different algorithms before assignments are applied in conservation or management. Further, we find no congruence between previously reported morphological differentiation and the sorting of microsatellite variation. Some introduced populations have retained much genetic variation while others have not, irrespective of morphology. Finally, we find alleles from the sympatric grey mongoose ( Herpestes edwardsii ) in one small Indian mongoose within the native range, suggesting an alternative explanation for morphological differentiation involving a shift in female preferences in allopatry.

Surface and Hyporheic Oligochaete Assemblages in a French Suburban Stream - Michel Lafont; Anne Vivier; Sylvie Nogueira; Philippe Namour; Pascal Breil (Hydrobiologia, 2006)

Displacement of an herbaceous plant species community by mycorrhizal and non-mycorrhizal Gmelina arborea, an exotic tree, grown in a microcosm experiment - Arsene Sanon; Pascal Martin; Jean Thioulouse; Christian Plenchette; Rodolphe Spichiger; Michel Lepage; Robin Duponnois (Mycorrhiza, 2006)

Importance of Assessing Population Genetic Structure before Eradication of Invasive Species: Examples from Insular Norway Rat Populations - JAWAD ABDELKRIM; MICHEL PASCAL; CLAIRE CALMET; SARAH SAMADI (Conservation Biology, 2005)
Determining the inter‐island migration abilities of pest species and delimiting eradication units enable more viable long‐term eradication campaigns because recurrent colonization from neighboring islands is avoided. We examined the genetic structure of the invasive Norway rat ( Rattus norvegicus ) to identify gene flow between islands and delimit population units at different geographical scales. We investigated variation in eight microsatellite loci in rat populations from 18 islands, representing five archipelagos off the Brittany coast (France). Although most of the islands are isolated from each other, short genetic distances, weak F ST values between close islands, and a high level of cross‐assignment showed that individuals collected on different islands could represent a single population unit. A Bayesian clustering method also supported the existence of high levels of gene flow between some neighboring islands. Thus, the statement “one island equals one population” can be false when inter‐island distances are less than a few hundred meters. Genetic studies enable the definition of island clusters among which migration may occur that should be considered eradication units. To avoid reinvasion and to minimize ecological and economic costs, rats on all islands in an eradication unit should be eradicated simultaneously. We suggest that the genetic monitoring we performed here can be applied for management of any pest.

Impact of subterranean fungus-growing termites (Isoptera, Macrotermitiane) on chosen soil properties in a West African savanna - Pascal Jouquet; Pierre Barré; Michel Lepage; Bruce Velde (Biology and Fertility of Soils, 2005)

Occupational risks for uveal melanoma results from a case-control study in nine European countries - Jean-Michel Lutz; Ian Cree; Svend Sabroe; Tine Kajsa Kvist; Lene Bjørk Clausen; Noemia Afonso; Wolfgang Ahrens; Terri J. Ballard; Janine Bell; Diane Cyr; Mikael Eriksson; Joëlle Févotte; et al. (Cancer Causes & Control, 2005)

French attempts to eradicate non-indigenous mammals and their consequences for native biota - Olivie Lorvelec; Michel Pascal (Biological Invasions, 2005)

Holocene turnover of the French vertebrate fauna - Michel Pascal; Olivier Lorvelec (Biological Invasions, 2005)

Spatial-temporal variability of ultraplankton vertical distribution in the Antarctic frontal zones within 60?66E, 43?46S - Cline Dubreuil; Michel Denis; Pascal Conan; Sylvie Roy (Polar Biology, 2003)

Differentiated thick ascending limb (TAL) cultured cells derived from SV40 transgenic mice express functional apical NHE2 isoform: effect of nitric oxide - Soline Bourgeois; Patrick Rossignol; Françoise Grelac; Cécile Chalumeau; Christophe Klein; Kamel Laghmani; Régine Chambrey; Patrick Bruneval; Jean-Paul Duong; Josiane Poggioli; Pascal Houillier; Michel Paillard; et al. (Pflügers Archiv - European Journal of Physiology, 2003)

Urine mutagenicity of farmers occupationally exposed during a 1-day use of chlorothalonil and insecticides - Véronique André; Pierre Lebailly; Didier Pottier; Edwige Deslandes; Michel De Méo; Michel Henry-Amar; Pascal Gauduchon (International Archives of Occupational and Environmental Health, 2003)

Molecular and biochemical characterization of an Arabidopsis thaliana arogenate dehydrogenase with two highly similar and active protein domains - Pascal Rippert; Michel Matringe (Plant Molecular Biology, 2002)

Why is the climate forcing of sulfate aerosols so uncertain? - Hu Rongming; Serge Planton; Michel Déque; Pascal Marquet; Alain Braun (Advances in Atmospheric Sciences, 2001)

Occupational risk factors, ultraviolet radiation, and ocular melanoma: a case–control study in France - Pascal Guénel; Laurent Laforest; Diane Cyr; Joëlle Févotte; Svend Sabroe; Cécile Dufour; Jean-Michel Lutz; Elsebeth Lynge (Cancer Causes & Control, 2001)

Is it worth eradicating the invasive pest Rattus norvegicus from Molène archipelago? Genetic structure as a decision-making tool - Claire Calmet; Michel Pascal; Sarah Samadi (Biodiversity and Conservation, 2001)

Early detection of staurosporine-induced apoptosis by comet and annexin V assays - Thierry Godard; Edwige Deslandes; Pierre Lebailly; Carole Vigreux; François Sichel; Jean-Michel Poul; Pascal Gauduchon (Histochemistry and Cell Biology, 1999)

Energetics of swelling in isolated hepatocytes: A comprehensive study - Anne Devin; Pascal Espié; Bernard Guérin; Michel Rigoulet (Molecular and Cellular Biochemistry, 1998)

Oxidative phosphorylation in intact hepatocytes: Quantitative characterization of the mechanisms of change in efficiency and cellular consequences - Xavier Leverve; Brigitte Sibille; Anne Devin; Marie-Astrid Piquet; Pascal Espié; Michel Rigoulet (Molecular and Cellular Biochemistry, 1998)

A QTL with major effect on milk yield and composition maps to bovine Chromosome 14 - Wouter Coppieters; Juliette Riquet; Juan-José Arranz; Paulette Berzi; Nadine Cambisano; Bernard Grisart; Latifa Karim; Fabienne Marcq; Laurence Moreau; Carine Nezer; Patricia Simon; Pascal Vanmanshoven; et al. (Mammalian Genome, 1998)

DNA methylation as a key process in regulation of organogenic totipotency and plant neoplastic progression? - Pascal Lambé; Hity Schié Nkung Mutambel; Jean-Gabriel Fouché; Roger Deltour; Jean-Michel Foidart; Thomas Gaspar (In Vitro Cellular & Developmental Biology - Plant, 1997)